Determinants of Inflation in GCC - Kandil, Magda (IMF Working Papers; Working Paper ;, 2009)
Inflationary pressures have heightened in the oil-rich Gulf Cooperation Council (GCC) since 2003. This paper studies determinants of inflation in GCC, using an empirical model that includes domestic and external factors. Inflation in major trading partners appears to be the most relevant foreign factor. In addition, oil revenues have reinforced inflationary pressures through growth of credit and aggregate spending. In the short-run, binding capacity constraints also explain higher inflation given increased government spending. Nonetheless, by targeting supply-side bottlenecks, the increase in government spending is easing capacity constraints and will ultimately help to moderate price inflation.